Biometrics for Personal Identification: Recapturing Ethics and Values in the Public Policy-Making Process - A Rawlsian Philosophical Analysis - Robert, Whitelaw (Université Saint-Paul / Saint Paul University, 2015)
Technological biometric advances for personal identification beyond fingerprints and iris scans, combined with national and international storage and exchange of personal information, raise ethical concerns. Philosophers and scholars have argued during the past century for increased involvement within policy-making. Through the work of John Rawls, a noted 20th century philosopher, the thesis examines appropriate and applicable ways to bridge the gap between philosophy and the practical requirements of public-policy making. Ethical considerations were absent during a 2003 Forum on Biometrics: Implications and Applications for a biometrics identity card. An outcome is the 2012 introduction of mandatory biometrics (digital facial photo and fingerprints) for visitor visa application documentation. Evidence also indicates continuing support for a Canadian biometrics identity card. Moreover, the technology is fast moving into the realm of “brain-reading” and the ethical question of “mind-privacy”. Nine words in a 1975 policy-making article by Albert Jonson and Lewis Butler are as potent today as first written forty years ago. “There appears to be no room for ethical experts.” The thesis seeks to recapture ethics within public policy-making.
Keywords: Biometrics; Ethics and Values; Policy-Making; John Rawls; Personal Identification; Thought privacy